Quantum technological dating of glacier ice from the last millennium and a new self-contained facility for routine measurements - Feng, Zhongyi (2019)
Abstract: The noble gas radioisotopes 85Kr, 39Ar and 81Kr are of great importance in radiometric dating because their half-lives cover time scales from the last millennium to one million years before present. They are present as inert trace gases in the atmosphere and the exchange with other environmental reservoirs makes them ideal tracers for hydrology, oceanography and glaciology. Their very low isotopic abundance is the huge hindrance for the detection and analysis. Especially in the case of argon with a natural abundance of 8x10^−16, classical decay counting requires tons of water or ice and measurement times of several weeks. To reduce the sample size, techniques from the field of quantum optics are applied to capture the atoms directly rather than rely on their decay signature. Argon Trap Trace Analysis is capable of daily measurements using samples as small as 0.5 mL STP argon and this is demonstrated here for glacier ice. A few kilograms of ice have been taken in artificial glacier caves and the measured argon ages are validated against preexisting constraints. These results and recent pilot studies have arisen a huge demand for small sample radio-argon dating. To meet this development, a second apparatus has been built in a self-sufficient laboratory container. The new machine is optimized for robustness and will increase the sample throughput capacities in the near-future. Furthermore, a setup has been built to characterize and improve the performance of the argon source, a main loss factor concerning efficiency
Weitere Stichwörter: Atom Trap Trace Analysis; ATTA
Keywords: Hochschulschrift